Electrochemistry of single droplets of inverse (water-in-oil) emulsions. Issue 24 (13th June 2017) - Zhang, Haozhi; Sepunaru, Lior; Sokolov, Stanislav V.; Laborda, Eduardo; Batchelor-McAuley, Christopher; Compton, Richard G.
Abstract : Single water droplet electrochemistry investigated for the first time, reveals the biphasic kinetics of ion transfer within water-in-oil emulsions. Abstract : We demonstrate the feasibility of electrochemically detecting individual water droplets dispersed in an oil phase (inverse emulsions) via the use of a redox probe confined in the droplet phase. The water droplets were tagged with potassium ferrocyanide, and were injected into an electrolyte cyclohexene/dichloromethane oil solution. Via simple cyclic voltammetry scans it is shown that single water droplets from a water-in-oil emulsion can be detected provided that rapid anion transfer from the oil to the water phase maintains electro-neutrality in the droplet.